INCREASING THE ONLINE SKILLS OF MSME PLAYERS THROUGH MARKETPLACE WORKSHOPS IN KENTENG VILLAGE, PURWANTORO DISTRICT - Mun Yah Zahiroh; Binti Mahmudah; Ivan Reza Devani Purwanto; Maya Roshidah (LP2M Universitas Ibrahimy, 2024)
Marketplace is an application that connects sellers and buyers in online transactions in cyberspace. Using marketplaces is a business strategy in the business world, considering complex problems, increasing competitors, and demands to keep up with global developments that require always being creative and innovative. In this digitalization era, the marketplace has a very important role for MSME players in boosting marketing increasing online sales turnover for branding and increasing market accessibility to expand market reach easily and quickly. However, the problem that occurs is that there are still many MSME players who are reluctant to jump into digital platforms. This is due to the difficulty of accessing the marketplace. This also happens in Kenteng Village where the majority of MSME players have not utilized the marketplace in selling products. Therefore, the solution that can be offered is by holding a workshop